The overvaluation of Renminbi undervaluation - Yin-Wong Cheung; Menzie D. Chinn; Eijii Fujii (Center for Economic Studies and ifo Institute (CESifo), 2007)
We evaluate whether the Renminbi (RMB) is misaligned, relying upon conventional statistical methods of inference. A framework built around the relationship between relative price and relative output levels is used. We find that, once sampling uncertainty and serial correlation are accounted for, there is little statistical evidence that the RMB is undervalued. The result is robust to various choices of country samples and sample periods, as well as to the inclusion of control variables.
Keywords: F31; F41; 330; Währung; Wechselkurs; Internationaler Wettbewerb; China